An ROI Ed-Biz Approach for Deploying Mobile Pedagogy - McConatha, Douglas (Mobile Pedagogy and Perspectives on Teaching and Learning, 2014)
An ROI Ed-Biz Approach for Deploying Mobile Pedagogy: 10.4018/978-1-4666-4333-8.ch015: The long history and short past of online distance education is posited as a precursor to the monumental changes revolutionizing global educational activity.
KerkoCite.ItemAlsoKnownAs: 10.4018/978-1-4666-4333-8.ch015 10/gf62h6 2129771:9WPFKMAZ